Upaya Pengembalian Kerugian Negara Melalui Kebijakan Pidana Uang Pengganti Tindak Pidana Korupsi - Artha Kariasmarico; Maroni Maroni; Emilia Susanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Criminal money substitution is a very important instrument and has a crucial role in efforts to recover state losses caused by corruption crimes. Through this mechanism, the state seeks to recover losses incurred due to corruption. Although there are provisions that regulate the crime of substitute money, the implementation of the substitute money policy in Indonesia is considered ineffective in restoring state losses due to corruption. The main problem in this study is how the substitute money policy in corruption in Indonesia today and how the construction of the substitute money criminal policy in the perspective of criminal law reform. The methods used in this study are normative juridical and empirical juridical which are research methods that combine normative legal elements with the addition of empirical data. The data sources used in this study are primary data and secondary data. Data was collected through literature studies and field studies. Based on the results of this study, it can be seen that the policy is considered not to clearly explain how the mechanism for recovering state losses through the penalty of substitute money is related. In practice, currently the return of state losses through the imposition of penalty money in lieu has not been effective. This is because there are still many obstacles. Some of the obstacles in the implementation of this substitute money crime are the limitations of law enforcement officials, lack of coordination between institutions, and the inability to trace and confiscate the assets of perpetrators of corruption crimes. In addition, another obstacle faced at the time of execution is the inability of the perpetrator to return state losses caused by corruption crimes. This is what causes the maximum implementation of the substitute money criminal policy. The construction of the substitute money criminal policy in the perspective of criminal law reform, namely the substitute money policy must be able to enforce the law in Total Enforcement or at least in Full Enforcement, namely demanding the return of all state losses caused by corruption crimes as a whole without any legal loopholes that allow convicts to evade.